Ointment Formulation of Tapak Dara (Catharanthus roseus (L.) G. Don) Flower Ethanol Extract and its Activity in Burn-Healing - Leny Leny; Tetty Noverita Khairani Situmorang; Rensus Siagian; Ihsanul Hafiz; Benni Iskandar (Borneo Journal of Pharmacy, 2023)
Treatment done on burn wounds is intended to provide local therapy to heal as quickly as possible. The content of secondary metabolites in the tapak dara (Catharanthus roseus (L.) G. Don) flower can help the healing process of burns, namely alkaloids, saponins, tannins, and flavonoids. Alkaloids act as antibacterial; saponins can trigger collagen formation; tannins as astringents that cause shrinkage of skin pores and stop minor bleeding in wounds; and flavonoids have anti-inflammatory effects. This study aimed to formulate an ointment of C. roseus flower ethanol extract and determine its physical characteristics such as organoleptic test, homogeneity, pH value, dispersion, and stability test of the preparation and examine the activity as a burn healer in white male rats. The research data were analyzed statistically using the ANOVA method, followed by the LSD test (least significant difference) to see how the ointment-containing extract reduced the diameter and percentage of the burn wounds. The results show that all ethanol extracts of C. roseus flower ointments met the requirements for its physical characteristic tests. It offers a good activity as a burn healer in white male rats. The most effective concentration is an ointment containing 15% of ethanol extract from C. roseus flower (F3 group), which shows a significant difference (p <0.05) from the blank and the other group formula in burn wound healing.